PELAKSANAAN PROGRAM PEMERINTAH DALAM PENINGKATAN KUALITAS AIR BERSIH DI PDAM KUTAI TIMUR - Maharani, Anissa Fitri (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. PDAM (Regional Drinking Water Company) as a business entity to meet the water needs of the community, however, the provision of water that has reliable quality uses a market approach so that it has a negative impact on the poor who are unable to reach the clean water services that have been provided. This study analyzes the implementation of government programs in improving clean water quality in East Kutai PDAM and the factors that affect the implementation of government programs in improving clean water quality in East Kutai PDAM. The implementation of government programs to improve clean water quality in PDAM East Kutai Regency is a strategic effort that aims to meet the basic needs of the community for proper and safe access to clean water. And the implementation of government programs in improving clean water quality in East Kutai PDAM is influenced by various internal and external factors. The central and local governments need to increase budget allocation for infrastructure improvements and stricter supervision and periodic evaluations of program implementation are needed to ensure that the goal of improving water quality is achieved. Keywords: Government, Clean Water, PDAM.